Formation of A Special Court for The Medical Profession Inrealizing the Aspirations of the Indonesian Doctors Association as Efforts to Develop National Health Law in Indonesia - Yandriza, Yandriza; Raspati, Lucky; Elvandari, Siska (Faculty of Law, Andalas University, 2025)
The object of this writing is based on the present, very often occurs among doctors, and or health workers proven to have made a mistake, and or medical negligence. Medical errors and or negligence can result in disability, and death of a patient. Disability and death of a patient cause thinking among doctors and/or health workers, it is considered that they have committed an alleged crime that endangers the safety of the body and life of a patient, so that doctors and/or health workers feel that they have been criminalized by certain parties. This criminalization is of course very confusing, considering that in fact in This criminal law perspective certainly cannot be said to be criminalization, in fact it can be said to be a form of criminal responsibility.